Дослідження методів рендерінгу користувацького інтерфейсу на базі фреймворків React та Svelte - Свиридов, В. Е. (ХНУРЕ, 2024)
In the era of rapid development of web technologies, the React and Svelte frameworks emerge not just as tools, but as key fundamental components of modern programming. Their role in web application development is defined not only by technical capabilities but also by a profound impact on the web industry ecosystem. These frameworks pave the way for creating innovative and dynamic interfaces, providing developers with advanced tools for implementing even the most complex projects. In this context, the significance of React and Svelte lies not only in providing convenient tools but also in transforming the approach to web development itself, which becomes a crucial factor in creating efficient, user-friendly, and scalable web applications.
Keywords: рендерінг; користувацький інтерфейс; React; Svelte